Psychological Impact of the Civil War and COVID-19 on Libyan Medical Students: A Cross-Sectional Study - Elhadi, Muhammed; Buzreg, Anis; Bouhuwaish, Ahmad; Khaled, Ala; Alhadi, Abdulmueti; Msherghi, Ahmed; Alsoufi, Ahmed; Alameen, Hind; Biala, Marwa; Elgherwi, Alsafa; Elkhafeefi, Fatimah; Elmabrouk, Amna; et al. (Frontiers in Psychology, 2020)
Abstract Objective We aim to determine the psychological status of medical students during the COVID-19 outbreak and civil war in Libya. Methods A cross-sectional study was conducted among medical students from 15 medical schools between April 20 and May 1, 2020. The demographic characteristics, generalized anxiety disorder 7-item (GAD-7) scale, and patient health questionnaire (PHQ-9) results were collected. Results Of the 3,500 students, 2,430 completed the survey. The mean (± SD) score of anxiety symptoms determined by the GAD-7 was 7.2 (5.1). A total of 268 (11%) students had a GAD-7 score of ≥15, which is indicative of moderate to severe anxiety. A total of 1,568 (64.5%) students showed different degrees of anxiety: mild, 910 (37.5%); moderate, 390 (16%); and severe, 268 (11%). Anxiety was significantly associated with living status and internal displacement (p < 0.05). The mean (+SD) score of depressive symptoms determined by the PHQ-9 was 9.7 (6.3). A total of 525 (21.6%) students had a PHQ-9 score of ≥15, which is indicative of moderate to severe depression. Approximately 1,896 (88%) students were diagnosed with mild (PHQ ≥ 5) depression. Moderate to severe depression was found in 525 (21.6%) students. Suicidal ideation was present in 552 patients (22.7%). Depression was only statistically associated with the year of study (p = 0.009). Conclusion These data highlight that medical students in Libya are at risk for depression, especially under the current stressful environment of the civil war and COVID-19 outbreak.